Da 'invenção' da homossexualidade ao discurso das posses: uma análise interpretativa da identidade homossexual - Pereira, Severino Joaquim Nunes (2009)
The study of the behavior of socially marginalized groups such as gays, Afro-descendents, slum dwellers and others is not easy but is extremely relevant to the consumer behavior field. Most studies about these groups focus basically on the dimension of a discriminated and excluded minority, neutralizing other dimensions such as that of 'consumers'. In doing so, this doctoral thesis seeks to investigate how the possessions-related discourse is used by gay males to deal with the stigma of homosexual identity at individual, family, group and social levels. It has been evaluated that homosexual identity and its related stigma Homosexuality, as well as the social constructions imposed by a medical discourse from the 19th century, have created the categorization of homosexuality. Participant observations with a gay male group and 20 semi-structured interviews have been performed from 2005 to 2008. Our results suggested that: (i) the culturally gay-built world seem to be divided between 'gay and heterosexual' worlds. Such division does not happen only in the gay imaginary but it can also be represented by products and possessions; (ii) some gay-consumption places have altered their meaning from profane to sacred meaning throughout consumption in the subject life’s; (iii) the body has been seen as a culture construction of and value in the gay world as well as it has been used as a sign of distinction and hierarchy.